Psycho-diagnostic study of the dyad «Mother-child»: prenatal and postnatal periods (The Journal of Psychology and Sociology, 2017)
This scientific article is devoted to research subjects of the dyad «mother-child» in the prenatal and postnatal periods. The aim of the study is to examine the specificity of the prenatal and postnatal periods, in particular, the study focuses on the personal psychological characteristics of pregnant women: the intensity of neuroses, somatic condition, the level of readiness for motherhood and the birth process, with regard to breastfeeding newborn and his level of the neonatal adaptation in the first days of extrauterine life. Individual features of the pregnant have an effect on the values of psychophysiological indicators of a newborn. In the course of this study, the relationship between high levels of alexithymia, depressive-anxiety syndrome, neuroticism, somatization and reduce adaptive abilities of the newborn in the extrauterine environment were detected.
Keywords: pregnancy; prenatal period; postnatal period; alexithymia; newborn; imprinting; personality traits.